2007 IEEE Sensors 2007
DOI: 10.1109/icsens.2007.4388660
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Gas Sensors Based on Quantum Cascade Lasers and Photonic Bandgap Hollow Waveguides

Abstract: In the present study, bending losses in conventional hollow waveguides (internally Ag/AgI coated) and in photonic bandgap (PBG) hollow waveguides (HWG) are compared based on studies via FT-IR spectroscopy and quantum cascade lasers (QCL). To date, literature on bending losses in hollow waveguides focuses on conventional HWG structures (e.g., silica structural tube with internal Ag/AgI coating), whereas the results discussed here compare relative bending losses in novel photonic bandgap waveguides, a new type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Coiling smaller diameter waveguides has been demonstrated to reduce the overall form factor, however, at the expense of sensitivity and robustness. Moreover, there are, to the best of our knowledge, no long-term studies reported that demonstrate how the internal mechanical bending stresses imposed onto structural materials and optical coatings in a coiled conventional HWG affect the overall lifetime of the HWG. Tubular devices depend on wet-chemistry for applying internal coatings, which significantly limits the coating options.…”
mentioning
confidence: 99%
“…Coiling smaller diameter waveguides has been demonstrated to reduce the overall form factor, however, at the expense of sensitivity and robustness. Moreover, there are, to the best of our knowledge, no long-term studies reported that demonstrate how the internal mechanical bending stresses imposed onto structural materials and optical coatings in a coiled conventional HWG affect the overall lifetime of the HWG. Tubular devices depend on wet-chemistry for applying internal coatings, which significantly limits the coating options.…”
mentioning
confidence: 99%
“…Modulated IR radiation periodically heats the sample gas, thereby producing a pressure wave detectable at acoustic frequencies as a function of analyte concentration. interaction path length, and radiation losses from bending the waveguide has to be determined [119].…”
Section: B Transducers 1) Hollow Core Waveguides Versus Conventional Gasmentioning
confidence: 99%
“…Details of the measurements are described elsewhere. 17 Caused by the photonic structure the Omniguide ® -fiber is only transmitting between 900 -1050 cm -1 . To compare with the QCL measurements the attenuations were determined at 10.34μm, and 50cm long straight fiber sections were used.…”
Section: Transmission Measurements With Thermal Emittersmentioning
confidence: 99%